KEPEMIMPINAN GLOBAL BERBASIS BUDAYA - Alfroki Martha; Wirma Datil Husna; Nurtika Syafitri; Dewi Oktavia; Titit putriani; Masidah Daulay (EDU RESEARCH, 2024)
Global leadership is the ability of individuals to inspire and motivate groups to achieve positive visions in an organized manner, while fostering growth both individually and collectively in the midst of complex global challenges. This article aims to explore the concept of global leadership that takes into account cultural differences between countries and organizations. This leadership is evolving in line with increasingly complex global dynamics, requiring leaders to have the ability to adapt to uncertainty, build diverse team connections, and maintain the basic principles of compromising with different cultural values. From this article, the concept of global leadership is examined which involves the ability of leaders to inspire groups in facing global challenges, with an emphasis on cultural differences. This article also discusses the relationship between leadership and culture, as well as the importance of a culture-based leadership approach to respond to social and cultural dynamics. Keywords: global leadership, culture, cultural intelligence and leadership strategy.